1996
DOI: 10.2307/3433170
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Benzene Metabolites on Differentiation of Bone Marrow Progenitor Cells

Abstract: Interleukin-3 (IL-3) and granulocyte/macrophage-colony-stimulating factor (GM-CSF) are responsible for maintaining survival and stimulating growth of early dormant hematopoietic progenitor cells (HPC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…The survival and proliferation of stem and progenitor cells are controlled by multiple growth factors, or cytokines, with overlapping functions that act individually or in combination to regulate hematopoiesis. A series of studies carried out in mice and in human bone marrow cultures have shown that benzene alters cytokine production or response to cytokines in the bone marrow (27)(28)(29)(30)(31)(32)(33)(34)(35). To determine if benzene exposure affects cytokine levels measured in peripheral blood, a more accessible and acceptable tissue source than bone marrow, we evaluated a panel of cytokines in the most heavily exposed workers and a subset of controls.…”
Section: Discussionmentioning
confidence: 99%
“…The survival and proliferation of stem and progenitor cells are controlled by multiple growth factors, or cytokines, with overlapping functions that act individually or in combination to regulate hematopoiesis. A series of studies carried out in mice and in human bone marrow cultures have shown that benzene alters cytokine production or response to cytokines in the bone marrow (27)(28)(29)(30)(31)(32)(33)(34)(35). To determine if benzene exposure affects cytokine levels measured in peripheral blood, a more accessible and acceptable tissue source than bone marrow, we evaluated a panel of cytokines in the most heavily exposed workers and a subset of controls.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that HQ stimulates proliferation of TF-1 cells via activation of the ERK/AP-1 signalling pathway together with concomitant increases in GM-CSF production and clonogenic response. In contrast, HQ enhancement of CFU response in human CD34 þ BM cells is dependent on the addition of exogenous rhGM-CSF, 7,8 but similarly is accompanied by AP-1 activation and an increase in GM-CSF production. Taken collectively, these studies suggest that HQ exerts many of its hematopoietic effects via alterations in the GM-CSF signaling pathway.…”
Section: Introductionmentioning
confidence: 87%
“…[4][5][6] We have also observed clonogenic enhancement in human CD34 þ BM cells treated in vitro with the BZ metabolite, hydroquinone (HQ), and then cultured in the presence of exogenous rhGM-CSF. 7,8 Cell proliferation is a wellrecognized risk factor in carcinogenesis; cell division resulting in a number of chemical and mechanical stresses that increase the likelihood of acquiring structural genomic changes. Individual malignancies, particularly hematopoietic and lymphoid cancers, often exhibit unique patterns or signatures of clonal lesions that are thought to play important roles in either the initiation or pathogenesis of these individual diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that benzene toxicity mainly results from its intermediate reactive metabolites (Irons and Stillman 1996;Kolachana et al 1993). Benzene is initially oxidized to benzene oxide by hepatic CYP2E1 in the liver (Koop et al 1989;Valentine et al 1996).…”
mentioning
confidence: 99%